A Faraday's law paradox. (6th December 2021) - Cross, Rod
Abstract: The voltage drop or potential difference across a resistor is easily measured with a voltmeter. However, if the loop formed by the resistor, the connecting leads, and the voltmeter surrounds a changing magnetic field then the measured voltage drop will be different. This result can lead to a paradox when using Faraday's law.